The Folklore Life of a Literary Text: Narration of The Tale of Tsar Saltan in Traditional Discourse - Ryko, Anastasia I. (SlovÄ›ne = Ð¡Ð»Ð¾Ð²Ñ£Ð½Ðµ. International Journal of Slavic Studies, 2017)
The article focuses on the retelling of Pushkinâ€™s The Tale of Tsar Saltan by an 80-year-old local woman, recorded at the end of the 20th century in the Novgorod region (northwest Russia). The text is analyzed both in terms of its structural aspect (the correspondence of prose narration, poetic quotations from Pushkinâ€™s text, and the narratorâ€™s comments) and in terms of its linguistic aspect (the correspondence of dialect and literary variants of grammatical forms). In comparison with Pushkinâ€™s original, in the retelling the authorâ€™s perspective has been changed from the fantastic to reality; consequently, the text has been transformed by the adaptation of elements alien to the familiar reality or by their replacement with familiar, but different, elements. Thus, the narrator included in the retelling several stories from her own life and the lives of her relatives (acquaintances), interiorizing the plot and filling it with personal and familiar realities, including transformations on the lexical level. The retelling retains features of a traditional folklore text. The plot becomes simplified; only the basic â€œevent-relatedâ€ points are kept, and detailed descriptions are excluded. The viewpoint of the narrator has also been changed from the external in The Tale of Tsar Saltan to internal in the retelling. In addition, some structural characteristics of the retelling, in comparison to Pushkinâ€™s original, are typical of oral speech. The narrator produced two versions of the retelling, the â€œmaleâ€ and the â€œfemaleâ€ version, told, respectively, to linguists of different genders. The versions are different at the level of the plot: the â€œmaleâ€ version describes the liberation of the Swan Princess, and in the â€œfemaleâ€ one, the narrator focuses on the revenge of Guidon that is directed toward his aunts. Thus, in the retelling, two folk plots, combined in Pushkinâ€™s original, are separated again and exist as two versions of the same text. Ð’ ÑÑ‚Ð°Ñ‚ÑŒÐµ Ñ€Ð°ÑÑÐ¼Ð°Ñ‚Ñ€Ð¸Ð²Ð°ÐµÑ‚ÑÑ Ð¿ÐµÑ€ÐµÑÐºÐ°Ð· ...